Food Policy 2017
DOI: 10.1136/jech-2017-ssmabstracts.92
|View full text |Cite
|
Sign up to set email alerts
|

OP93 Stakeholders’ framing of evidence about the uk sugar-sweetened beverage tax: a news media analysis

Abstract: BackgroundIn politically-contested health debates, such as sugar-sweetened beverage (SSB) taxation, stakeholders seek to present evidence and arguments for or against the specific policy initiatives, based on their interests. The news media play a crucial role in shaping public opinion by selectively choosing which messages to focus on. While the literature suggests that media debates should be a key concern for those interested in understanding public health policy processes, as yet there has been only limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We found that, for our audience, education and information is a critical component for an SSB-free policy to achieve community acceptance and support. Despite the many similarities between SSB and tobacco control,[23,24] this is an important area of difference; while the harms of tobacco are well understood and widely accepted, it is not currently the case with SSBs[25,26].…”
Section: Resultsmentioning
confidence: 99%
“…We found that, for our audience, education and information is a critical component for an SSB-free policy to achieve community acceptance and support. Despite the many similarities between SSB and tobacco control,[23,24] this is an important area of difference; while the harms of tobacco are well understood and widely accepted, it is not currently the case with SSBs[25,26].…”
Section: Resultsmentioning
confidence: 99%